2015
DOI: 10.1093/cercor/bhv154
|View full text |Cite
|
Sign up to set email alerts
|

Early Cerebellar Network Shifting in Spinocerebellar Ataxia Type 6

Abstract: Spinocerebellar ataxia 6 (SCA6), an autosomal dominant degenerative disease, is characterized by diplopia, gait ataxia, and incoordination due to severe progressive degeneration of Purkinje cells in the vestibulo- and spinocerebellum. Ocular motor deficits are common, including difficulty fixating on moving objects, nystagmus and disruption of smooth pursuit movements. In presymptomatic SCA6, there are alterations in saccades and smooth-pursuit movements. We sought to assess functional and structural changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 101 publications
(121 reference statements)
0
32
0
Order By: Relevance
“…The alteration of the brain network is found to be associated with disease severity and disease duration in SCA1 (Solodkin et al, 2011), cognitive and motor performance (Hernandez-Castillo et al, 2015) and onset of parkinsonism in SCA2 (Wu et al, 2013), visual task performance in SCA6 (Falcon et al, 2015) and CAG repeat length in SCA7 (Hernandez-Castillo et al, 2013). These studies, although mostly based on fMRI, suggest that brain network alteration is associated with clinical variables such as the CAG repeat length, disease severity, disease duration, and task performance in SCAs.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of the brain network is found to be associated with disease severity and disease duration in SCA1 (Solodkin et al, 2011), cognitive and motor performance (Hernandez-Castillo et al, 2015) and onset of parkinsonism in SCA2 (Wu et al, 2013), visual task performance in SCA6 (Falcon et al, 2015) and CAG repeat length in SCA7 (Hernandez-Castillo et al, 2013). These studies, although mostly based on fMRI, suggest that brain network alteration is associated with clinical variables such as the CAG repeat length, disease severity, disease duration, and task performance in SCAs.…”
Section: Discussionmentioning
confidence: 99%
“…The significant activation of these regions beyond cerebellar activation in SCA3 patients might also represent a mechanism of compensation. This whole‐brain mechanism is reminiscent of the early intracerebellar network shifting that is observed in spinocerebellar ataxia type 6 [Falcon et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been validated as reliable in prior work (Planetta et al 2015b; Prodoehl et al 2013). Based on previous findings (Falcon et al 2015; Vaillancourt et al 2006), we selected seven ROIs important for visually-guided motor control and the size for each ROI was determined to cover the anatomy for all participants: (a) dentate nucleus (bilateral; 20 voxels), (b) superior cerebellar peduncle (bilateral; 14 voxels), (c) middle cerebellar peduncle (bilateral; 16 voxels), (d) inferior cerebellar peduncle (bilateral; 10 voxels), (e) lobule V (bilateral; 68 voxels), (f) lobule VI (bilateral; 125 voxels), and (g) vermis (42 voxels). Using the ROIs, we extracted the FA T and free-water values.…”
Section: Methodsmentioning
confidence: 94%
“…Across seed placed in bilateral M1, SMA, and contralateral S1, SCA6 patients showed decreased task-based functional connectivity between cortico-cortical regions (M1 vs. SMA) and cortical-cerebellar regions (M1 vs. Vermis VI and SMA vs. lobule V–VI). Falcon and colleagues reported that effective connectivity between visual-related cortex and intermediate and lateral cerebellum was reduced in individuals with more severe ataxic symptoms compared with healthy controls, presymptomatic, and mild SCA6 patients (Falcon et al 2015). Our current findings provide new evidence that functional connectivity is also impaired in SCA6 in motor-related regions of the cortex and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation